Respuestas

2013-08-23T14:14:08+02:00
Fernando,
Vamos a traducir el enunciado a lenguaje matemático:
 Sea el número N
                             4N - (N/3 - 4) = 3(N/2 + 10)
Efectuando
                             4N - N/3 + 4 = 3/2N + 30
Resolviendo:
                             4N - N/3 - 3/2N = 30 - 4
                             1/6(24 - 2 - 9)N = 26
                                       1/6(13N) = 26
                                             13N = 26x6
                                                 N = 12
El número es 12